Effect of influenza vaccination in solid organ transplant recipients: A nationwide population‐based cohort study. Issue 10 (16th May 2022) - Harboe, Zitta Barrella; Modin, Daniel; Gustafsson, Finn; Perch, Michael; Gislason, Gunnar; Sørensen, Søren Schwartz; Rasmussen, Allan; Biering‐Sørensen, Tor; Nielsen, Susanne Dam
Abstract : Vaccination can prevent influenza in solid organ transplant (SOT) recipients. Using a modified season‐specific approach over nine consecutive influenza seasons, we investigated influenza vaccination coverage and effectiveness in a population‐based nationwide cohort study that included all SOT recipients aged ≥18 years who were living in Denmark from December 1, 2007 to April 1, 2016. The primary outcome was the season‐specific risk of all‐cause pneumonia admission. Secondary outcomes were season‐specific influenza‐related admission, intensive care unit (ICU) admission, and all‐cause mortality. Crude and adjusted hazard ratios (aHRs) with 95% confidence intervals (CIs) were estimated using Cox proportional hazards regression models. In total, 11 381 person‐years of follow‐up data were collected from 5745 SOT recipients, 48% of whom were vaccinated. Influenza vaccination was associated with a reduced risk of all‐cause pneumonia admission (aHR, 0.83; 95% CI, 0.69–0.99; p = .035) and all‐cause mortality (aHR, 0.60; 95% CI, 0.47–0.76; p = .001), but not influenza‐related admission (aHR, 0.75; 95% CI, 0.46–1.22; p = .24) or ICU admission (aHR, 0.84; 95% CI, 0.67–1.06; p = .14) during the same season. Despite these benefits, uptake of influenza vaccination among SOT recipients was low. Therefore, annual influenza vaccination needs to be prioritized. Abstract : This nationwide cohort study over nine consecutive influenza seasons shows that seasonal influenza vaccination is associated with reduced risk of hospitalization for all‐cause pneumonia but that less than half of all solid organ transplant recipients were vaccinated.